Phytotherapy and ethnopharmacology in dentistry - Bueno, Carlos Roberto Emerenciano [UNESP]; da Silva, Ana Cláudia Rodrigues [UNESP]; Dezan-Júnior, Elói [UNESP] (My University, 2024)
Since dawn of time, mankind has used plants as a source of natural products to treat several diseases, due to herbal active compounds that interact with the human body, consolidating plants extracts as folk medicine. According to the World Health Organization (WHO), drugs originated from medicinal plants extracts are the largest source of medicine used by near 80% of developing countries population. In dentistry, the association of plant extracts with cariology, restorative dentistry, endodontics or periodontics is used to reduce inflammation, enhance antimicrobial agents, as antiseptics, antifungals, analgesics or even as mouth rinse to act on dental plaque. In cariology, the use of herbal therapy is proposed in different stages of dental caries disease, whether in diagnosis, prevention or treatment. In endodontics, phytotherapics may act as coadjutant in irrigating solutions, intracanal medication, obturating sealer, repair cement or even in bone regeneration after apical surgery. In periodontics, gels, chips and extracts containing herbs showed potential benefits when used as adjuvants to scaling and root planning. Other applications of plant extracts in dentistry have been proposed as storage media for avulsed teeth, as anesthetic and hemostatic agent
Keywords: Dentistry; Endodontics; Medicinal plants; Phytotherapy; Plant extracts